Local and Traditional Knowledge in Watershed Governance ... : tracking change Local and Traditional Knowledge in Watershed Governance ... - Tracking Change (University of Alberta Library, 2017)
Tracking Change… is a new research initiative funded by the Social Sciences Humanities Research Council of Canada and led by the University of Alberta, the Traditional Knowledge Steering Committee of the Mackenzie River Basin Board, the Government of the Northwest Territories and many other valued partner organizations. Over six years (2015-2022), the project will fund local and traditional knowledge research activities in the Mackenzie River basin and sister projects in the Lower Amazon and Lower Mekong River Basins, with the long term goal of strengthening the voices of subsistence fishers and Indigenous communities in the governance of major fresh water ecosystems. The project developed in recognition that river systems are important social, economic, cultural and ecological places that contribute to the well-being of communities in diverse ways. River peoples, particularly Indigenous peoples who have well developed fishing livelihoods can offer extremely valuable insights about long term (historic and ...